South American Acanthocinini (Coleoptera, Cerambycidae, Lamiinae): new species, synonymy, description of females, and notes - Monné, Miguel A.; Botero, Juan Pablo; Olivier, Renan Da Silva; Santos-Silva, Antonio (Zootaxa, 2024)
Eucharitolus Bates, 1885 is divided into two informal groups of species, and its provisional features are reported. The females of Eucharitolus longus Botero & Monné, 2012, and Xenocona senticosa (Monné & Martins, 1976) are described for the first time and both species are newly recorded from Bolivia. New state records are provided for Eucharitolus lituratus (Melzer, 1934) and E. spilotus Botero & Monné, 2012. Eucharitolus geometricus (Tippmann, 1960) is transferred to a new genus, which is included in a previous key. A new species of Eucharitolus, E. thomazi, is described from Brazil (São Paulo) and an updated key to the genus is provided. Lepturdrys Gilmour, 1960 is reinstated and a new species, L. capixaba, is described from Brazil. Notes and new record for Lepturges (Lepturges) melzeri Gilmour, 1959 are provided. Urgleptes ovalis (Bates, 1866) is transferred to Lepturges (Lepturges) Bates, 1863. A new species of Lepturges (Lepturges), L. (L.) dubius, is described from Bolivia; Nealcidion zigzag sp. nov. is described from Bolivia. Lophopoeum paiolai Monné et al., 2023 is synonymized with L. kawense Roguet, 2022, and a new country record is provided. Misidentifications of Lophopoeum meridianum Fisher, 1938, L. fuliginosum Bates, 1863, and L. bimaculatum (Gilmour, 1961) are reported. The presence of erect setae on elytra of the type species of Lophopoenopsis Melzer, 1931 is reported for the first time, and the genus is included in a previous key.